Turcos e portugueses: an oral history of 'national' identity and football in Galicia - McGinn, Matt (2024)
This thesis explores the relationship between ‘national’ identity and football in Galicia, north-west Spain. The research is based on an oral history of football supporters in Galicia and the Galician diaspora in the United Kingdom, with a focus on 1987 to 2005. This period saw unprecedented success for Galician football clubs Deportivo La Coruña, Celta Vigo, and Compostela, which coincided with significant electoral gains for Galician nationalist parties. Yet there is limited scholarship on the lived experience of Galician identity and its expression through football. I argue that football allowed Galicians to negotiate and (re)articulate multiple identities – civic, ‘national’, and state – which often overlapped or competed with one another. The use of football to imagine Galicia was sometimes oppositional in tone; football served to differentiate Galicia from perceived adversaries. On other occasions it was affective; football encouraged the performance of kinship with other communities. In both cases, participants shared the conviction that football can effect political and social change in Galicia. This research has two main implications. First, I contribute to scholarship on the interaction between football and sub-state identity, where multiple identities make sport an arena for competing notions of belonging. Second, in using oral history methodology, I contribute a bottom-up perspective of how and why civic and national mythologies capture the imagination (or fail to do so), based on personal, subjective narratives